Peran Manajemen Konflik dan Cara Penanganan Konflik dalam Organisasi Sekolah (Studi Literature) - Moh Amin Indra Kusuma; Hairunisa Hairunisa; Fajar Zikiri Ramadhan; Rokhim Setyawan Utomo; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The main problem in this study is how conflict management can be applied effectively in school organizations. The discussion of this study uses the literature review method. The data obtained are processed by reviewing scientific journals and books related to the topic. This study aims to provide a better understanding of the role of conflict management in school organizations and to identify effective strategies in handling conflicts. The findings of this study are that determining the approach and strategy of conflict management is very important, namely with open communication. In addition, the role of the principal is also very important and needs to improve skills and attend training on conflict management. The implications of this conflict management can minimize stress in school organizations.